Kuantifikasi Perubahan Kadar Nitrogen Total di Tanah dan Jaringan Tanaman Kedelai (Glycine max (L.) Merrill) Varietas Anjasmoro selama Proses Budidaya - Shinta Palupi (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2026)
Nitrogen is an essential element for soybean growth, particularly in the formation of vegetative organs and seed protein. The nitrogen requirement of soybean plants varies according to their growth stages. This study aimed to quantify nitrogen levels in soil and plant tissues of Anjasmoro soybean variety over a 13-week cultivation period. Observations were conducted weekly by collecting soil and plant samples from three randomly selected polybags. Nitrogen analysis was performed using a colorimetric Kjeldahl method. The results showed that nitrogen supply was obtained not only from soil media and fertilizers, but also from biological nitrogen fixation facilitated by symbiotic microbes forming root nodules as well as non-symbiotic soil microbes. The lowest total soil nitrogen content was recorded at 0 weeks after planting (WAP) at 0.20%, while the highest was observed at 7 WAP at 0.82%. The lowest total nitrogen content in plant tissue occurred at 8 WAP at 1.80%, whereas the highest was recorded at 4 WAP at 8.07%. Soybean plants experienced etiolation due to suboptimal light intensity, resulting in a vegetative phase that was prolonged by two weeks. Nitrogen uptake during this extended vegetative period reached 4.6%. The average total nitrogen absorbed by the plants during cultivation was 2.881 g per plant, while total nitrogen accumulation in the system increased by 26.285 g per plant.